Solito, solita : crossing borders with youth refugees from Central America - Mayers, Steven; Freedman, Jonathan, 1950-; Zamora, Javier (Voice of witness (Chicago, Ill.), 2019)
Provides a collection of oral histories that tells--in their own words--the stories of young refugees fleeing countries in Central America and traveling for hundreds of miles to seek safety and protection in the United States. Fifteen narrators describe why they fled their homes, what happened on their dangerous journeys through Mexico, how they crossed the borders, and for some, their ongoing struggles to survive in the United States. In an era of fear, xenophobia, and outright lies, these stories amplify the compelling voices of migrant youth. --From publisher description.